Rancang Bangun M2M (Machine-to-Machine) Communication Berbasis 6LoWPAN - Doni Pradana; Bakhtiar Alldino Ardi Sumbodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
At the present time the development of technology enabling communication services without the use of cables its called wireless technology. One such wireless communication technology is M2M (Machine to Machine) communication. In this study, using a protocol 6LoWPAN as the basis of M2M communications, becaused in Zigbee protocol encountered to the weakness such as the value of end-to-end delay and packet loss is greater than 6LoWPAN protocol. Work on this study is desaign system of M2M communication based on 6LoWPAN protocol and compare the data of the performance of 6LoWPAN protocol with Zigbee protocol terms of end-to-end delay and packet loss. Variations of testing is to set the baud rate Xbee 1200 bps, 4800 bps, 9600 bps, 19200 bps, 38400 bps, 57600 bps, 115200 bps. Besides the baud rate, the variation also adjusting the distance between nodes from 10 meter up to 60 meter by 10 meter intervals. Average of end-to-end delay time is 1899 milliseconds on 6LoWPAN, while protocol Zigbee is 422 miliseconds. In the packet loss aspect, in 6LoWPAN protocol not provided because the use of UDP not have an acknowledgement and squence number to track packet loss, while average of packet loss Zigbee protocol is 26%.